The Influence of Injection Molding Parameter on Properties of Thermally Conductive Plastic - Hafizah Azis N.; Zulafif Rahim M.; Sa'Ude N.; Rafai N.; Yusof M.S.; Tobi A.L.M.; Sharif Z.M.; Rasidi Ibrahim M.; Ismail A.E. (Institute of Physics Publishing, 2023)
Conductive plastics; Copper; Copper powder; Design of experiments; Molding; Nozzles; Powder metals; Tensile strength; Thermal conductivity; Injection moulding machine; Injection parameters; Injection pressures; Injection-molding parameters; Mass manufacturing; Nozzle temperature; Plastic composites; Plastic materials; Injection molding